Analisis Strategi Marketing Pada Bisnis Rumah Sakit Untuk Meningkatkan Kepuasan Pelanggan - Sari, Meci Nilam (STMIK Amika Soppeng, 2023)
In the last few years, business in the field of health services, especially hospitals in Indonesia has grown very rapidly. This can be seen from the emergence of various private hospitals in big cities to remote areas with various models offered, some are individual, network hospitals, to hospitals with international labels. Analysis of marketing strategies that can be used by hospitals to increase customer satisfaction is from the quality of human resources, service quality, corporate image, and ends with consumer satisfaction in using products and services at the hospital itself. Having quality human resources will produce good service quality, and can create a good corporate image in the eyes of consumers, so that customer or patient satisfaction will be created to continue using products and services at the hospital itself.